The mediator role of unmet needs on quality of life in myeloma patients - Pereira, M. G. (2022)
Purpose: The diagnosis of multiple myeloma (MM) has a significant impact on patients. This study analyzed the mediating role of patients' unmet needs in the relationship between psychological morbidity/social support and quality of life (QoL). Methods: This study included 213 patients with MM recruited from the outpatient medical oncology and clinical hematology services from five hospitals. Patients who meet the study criteria were referred by physicians and invited to participate in the study by the researcher. All participants answered the following questionnaires: Hospital Anxiety and Depression Scale, Satisfaction with Social Support Scale, Short-Form Survivor Unmet Needs Survey, and The European Organization for Research and Treatment of Cancer's Multiple Myeloma Module. Descriptive statistics, bivariate correlations, and structural equation modeling were performed to analyze the data. Results: The indirect effect of psychological morbidity on patients' future perspectives (MYFP) was partially mediated by information unmet needs (INF), while the indirect effect of psychological morbidity on treatment side effects (MYSE) was partially mediated by relationship and emotional unmet needs (REH). In turn, the indirect effect of psychological morbidity on disease symptoms (MYDS) was fully mediated by REH. Social support had an indirect effect on MYDS and MYSE fully mediated by REH. Conclusion: Intervention programs tailored to promote MM patients' QoL should specifically address information and emotional needs, raising awareness and training health professionals, caregivers, and family members to attend MM patients' unmet needs.